Clinical expressive arts therapy in theory and practice : psychodynamic snapshots - Goren-Bar, Avi (Cambridge Scholars Publishing, 2019)
This volume makes a tremendous contribution to the field of expressive arts therapy through its presentation of clear and profound theoretical bases to a relatively new profession in the domain of psychotherapy. It applies comprehensive, in-depth psychological knowledge to practical cases which shed light on clinical interventions that reflect the use of art in psychotherapy. The book provides a fruitful and much needed theoretical kaleidoscope to the professional community of expressive arts therapy.